Improved physiological and morphological traits of root synergistically enhanced salinity tolerance in rice under appropriate nitrogen application rate - Chen, Yinglong; Liu, Yang; Ge, Jianfei; Li, Rongkai; Zhang, Rui; Zhang, Yang; Huo, Zhongyang; Xu, Ke; Wei, Huanhe; Dai, Qigen (Frontiers in Plant Science, 2022)
Numerous papers studied the relations between nitrogen rate and rice yield in saline soils, whereas the rice root morphological and physiological characteristics mediating nitrogen rates in yield formation under varied salinity levels remain less concerns. Through a field experiment applied with five nitrogen rates (0, 210, 255, 300, 345, and 390 kg ha–1) in saline land, we found that rice yield peaked at 7.7 t ha–1 under 300 kg ha–1 nitrogen, and excessive N was not conductive for increasing yield. To further elucidate its internal physiological mechanism, a pot experiment was designed with three N rates (210 [N1], 300 [N2], 390 [N3] kg ha–1) and three salt concentrations (0 [S0], 1.5 [S1], 3.0 [S2] g kg–1 NaCl). Results showed that the average grain yield was decreased by 19.1 and 51.1% under S1 and S2, respectively, while notably increased by 18.5 and 14.5% under N2 and N3, respectively. Salinity stress significantly inhibited root biomass, root length and surface area, root oxidation capacity (ROC), K+ and K+/Na+ ratio, and nitrogen metabolism-related enzyme activities, whereas root Na+ and antioxidant enzyme activities were notably increased. The mechanism of how insufficient N supply (N1) affected rice yield formation was consistent at different salinity levels, which displayed adverse impacts on root morphological and physiological traits, thereby significantly inhibiting leaf photosynthesis and grain yield of rice. However, the mechanism thorough which excessive N (N3) affected yield formation was quite different under varied salinity levels. Under lower salinity (S0 and S1), no significant differences on root morphological traits and grain yield were observed except the significantly decline in activities of NR and GS between N3 and N2 treatments. Under higher salinity level (S2), the decreased ROC, K+/Na+ ratio due to increased Na+, antioxidant enzyme activities, and NR and GS activities were the main reason leading to undesirable root morphological traits and leaf photosynthesis, which further triggered decreased grain yield under N3 treatment, compared to that under N2 treatment. Overall, our results suggest that improved physiological and morphological traits of root synergistically enhanced salinity tolerance in rice under appropriate nitrogen application rate.